Use of mesh fixation device in inguinal hernia - Kumar Singhal, Vinod; Alaswad, Faris Dawood; Ojha, Varsha; Vinod Singhal, Vidher Varsha (International Surgery Journal, 2023)
Background: With attention to patient outcome after open inguinal hernia chronic inguinal region pain and discomfort are major complains due to nerve compression by sutures used for mesh fixation. Objectives to compare outcomes of mesh fixation with metallic versus delayed absorbable suture material in inguinal hernia through laparoscopic surgery. Methods: This was prospective study conducted at department of general surgery in a Prime hospital, Dubai during the period of January 2022 to December 2022. Prior approval of local ethical committee was obtained. Total 100 male patients who underwent laparoscopic surgery were included in the study. Patients were split into two groups of 50 each. Metallic suture material (Tantallum 1-0) was used to fix the mesh in group 1 while mesh fixation was used in group 2 was completed with Vicryl 2-0, a delayed absorbable suture material. SPSS was used for analysis. Results: There was appearance of post-operative pain in 20 patients, 10 patients, and 7 patients after 10 days, after 1 month and after 3 months, respectively in group 1 while for group 2, post-operative pain appeared in 12 patients, 4 patients, and 2 patients after 10 days, after 1 month and after 3 months, respectively. As such there was no statistically significant difference was found between two groups except for the appearance of the post-operative pain after 1 month (p<0.05). Conclusions: The recurrence rates for the two approaches are statistically equivalent. As a result, delayed absorbable material may be an effective mesh fixation substitute.